Long-Run Structural and Productivity Change in U.S. Agriculture: Effects of Prices and Policies - Robert E. Evenson; Wallace B. Huffman (Yale University, Economic Growth Center, 1997)
Long-Run Structural and Productivity Change in U.S. Agriculture: Effects of Prices and Policies by Wallace E. Huffman and Robert E. Evenson The paper presents (1) a conceptual framework for structural change when farms may be multiproduct or specialized and (2) an econometrics examination of causes of structural and total factor productivity (TFP) change for U.S. agriculture. Farm size, farm specialization, and part-time farming are the structural dimension emphasized, and they become potential channels to TFP change. Using state aggregate data starting in 1950, we conclude that input prices, public and private research, public extension, and government commodity programs have directly and indirectly caused change in U.S. farm structure and TFP. Our results suggest that changes in farm size, however, have been dominated by input price changes rather than by technology or government programs.
Keywords: 330; farm structure; productivity; farm size; farm specialization; part-time farming; research; technical change; agriculture; Produktivität; Strukturwandel; Landwirtschaft; USA